Load Frequency Control for Small Hydro Power Plants Using Adaptive Fuzzy Controller - Ozbay, Ebru; Gencoglu, Muhsin Tunay (Ieee, 2010)
Electrical energy generation is very important due to the increasing energy need. To satisfy the need, small scale hydro power plants are constructed in addition to large scale hydro power plants. Hydro power plants have a significant role in the generation of electrical energy. Small hydro power is a kind of clean and renewable energy sources. Small hydro power has a big potential in most areas of the world. This article proposed a novel model design for small hydro power plant (SHPP) using linear and nonlinear turbine model without surge tank effects. The model was created using adaptive fuzzy logic controller. The aim of this article is to improve their implementations by developing a SHPP model without using conventional control methods. The conventional control methods require choosing individual P and I parameters for each load value whereas in the developed model this process carried out by means of a single equations by using adaptive fuzzy logic controller.
IEEE International Conference on Systems, Man and Cybernetics -- OCT 10-13, 2010 -- Istanbul, TURKEY
Keywords: hydro power plant; linear and nonlinear turbine model; adaptive fuzzy controller